Strategi Pemasaran Menggunakan Fitur Shopee Live Streaming Sebagai Media Promosi Untuk Meningkatkan Daya Tarik Konsumen ( Studi Kasus Thrift Shop di Kabupaten Tulungagung ) - Adinda Ayu Puspita Sari; Muhammad Alhada Fuadilah Habib (Jurnal Ilmiah Wahana Pendidikan, 2023)
Increasingly sophisticated technological developments have made it easy for business people to do business. One of them is with digital marketing or better known as digital marketing. Digital marketing is one of the methods used by someone to maintain or increase consumers and market share in today's global era. There are many social media platforms and marketplaces that can be used to market a product such as the Shopee Marketplace which has various features, one of which is Shopee Live Streaming. Shopee Live is a feature on the shopee platform that allows sellers to create live streaming sessions selling their stores and products in real time. This study aims to analyze marketing strategies using the Shopee live streaming feature as a promotional medium to increase consumer appeal. The research method used is descriptive qualitative with data sources obtained from interviews, observation, and documentation. Based on the research that has been done, the results show that the marketing strategy of using the Shopee live streaming feature as a promotional medium to increase consumer appeal has been successfully carried out with several strategies such as display products live, using good and clear video backgrounds and lighting, holding discounts and give aways, using property or an attractive background so that viewers are interested in seeing the shopee live streaming displayed, using an attractive profile, title, and appearance, so that the audience is interested in entering the shopee live streaming room, always pay attention to the layout of the camera and good products, because if the layout messy cameras and products will make viewers or buyers uncomfortable watching live streaming.